The Effect of Service Quality on Customer Satisfaction at PT. PLN (Persero) Amuntai Customer Service Unit - Nurul Hasanah; Ary Yudianto; Haris Fadillah; Santi (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: This research at the PT. PLN (Persero) Amuntai Customer Service Unit aims to determine if customer satisfaction is impacted by service quality. The results of a basic linear regression statistical analysis were processed using SPSS statistics software version 22.0 as part of the quantitative methodology of this investigation. For this study, the sample consisted of 40 respondents. Among the analytical methods used in this study are the determination coefficient (R2), the t test (partial test), the validity and reliability tests, the basic linear regression analysis, and the traditional assumption test (normality). The results of the investigation show that the service quality variable has a positive and substantial influence on PT. PLN (Persero) ULP Amuntai's customer satisfaction. The correlation coefficient (R) of 0.965 shows a substantial and positive association between customer satisfaction (Y) and service quality (X). The fundamental linear regression equation that was generated is Y = - 2.250 + 0.603X. The t-test (partial test) findings revealed that Ha was accepted whereas H0 was rejected, with the computed t-value being 22.724 > the table t-value of 1.685 and the significance value being 0.000 < 0.05. At PT. PLN (Persero) ULP Amuntai, the first hypothesis—that service quality has a positive and significant impact on customer satisfaction—has been validated and approved